2015
DOI: 10.1111/cars.12076
|View full text |Cite
|
Sign up to set email alerts
|

The Rise and Stall of Canada's Gender‐Equity Revolution

Abstract: The growing symmetry in gender roles is a revolutionary change as consequential as technological advances and globalization. We illustrate how the social world in Canada has changed for women and men over the course of the last century, both in terms of greater gender equity and of policies supporting equity. However, some of the significant changes that occurred in the last 100 years have recently stalled, while the overall progress has been uneven for certain subgroups. We suggest reasons for both the stalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…Moreover, differences between young males and females’ norm perceptions (top half Table 2 , last column) indicated that young females estimated men’s current career investment significantly higher than young males do, and they perceived prescriptive norms to indicate more strongly that men should invest in a career and that women should invest in a family. Thus, young females perceived gender norms to be even more traditional than young males, which could be explained by the fact that women experience more disadvantages from traditional gender divisions than men (Eagly et al, 2000; England, 2010, 2011; Gerson, 2010). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, differences between young males and females’ norm perceptions (top half Table 2 , last column) indicated that young females estimated men’s current career investment significantly higher than young males do, and they perceived prescriptive norms to indicate more strongly that men should invest in a career and that women should invest in a family. Thus, young females perceived gender norms to be even more traditional than young males, which could be explained by the fact that women experience more disadvantages from traditional gender divisions than men (Eagly et al, 2000; England, 2010, 2011; Gerson, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, societal changes lead women especially to increasingly consider “having it all,” that is, pursuing a successful career and family life (Hoffnung, 2004). Indeed, in the last decades, women’s career involvement has increased greatly (England, 2010, 2011), while at the same time women continue to have the main responsibility for family tasks (Hochschild and Machung, 2012; European Commission, 2014). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Men more often run in ridings where winning is likely and where their chances of getting re-elected remain high from election to election. Guppy's and Luongo's (2015) analysis of gender trends in politics suggested that the gender equity movement in Canada has "stalled" (p. 241). With less than one quarter of House seats occupied by women in 2014, Canada's parliament was ranked 61st in the world for gender equality in federal politics (p. 250).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since a heavy majority of politicians in Canada are male (Guppy & Luongo, 2015) and this majority is carried into media newsrooms (Women's Media Center, 2015), messages pass through a double lens of male perspective before being presented to a general audience.…”
Section: Role Of the Mediamentioning
confidence: 99%